Pengaruh Profitabilitas, Carbon Emission Disclosure, dan Green Accounting terhadap Nilai Perusahaan - Setianingsih, Novie Astuti; Asmoro, Wiwiek Kusumaning; Putranti, Eti; Andari, Atik Tri (Gorontalo Accounting Journal, 2025)
This study aims to analyze the effect of profitability, green accounting, and carbon emission disclosure on firm value in the mining sector listed on the Indonesia Stock Exchange. This research employs a quantitative approach with a sample of 32 mining companies during the 2021–2024 period, selected using a purposive sampling method. Data analysis was conducted using descriptive statistics, classical assumption tests, and multiple linear regression analysis. The results show that profitability and carbon emission disclosure have a positive and significant effect on firm value, while green accounting has no significant effect. These findings indicate that investors tend to place greater value on financial performance and environmental transparency than on the implementation of green accounting practices in determining firm value.